Radiologische und nuklearmedizinische Diagnostik und Therapie der Schilddrüsenerkrankungen: Teil II: Maligne Erkrankungen der Schilddrüse - Zechmann, Christian; Haufe, Sabine (Der Radiologe, 2012)
Malignant thyroid diseases have increased in recent years. The distinction between differentiated and non-differentiated thyroid carcinoma is essential for therapy and follow-up. The frequently diagnosed papillary and follicular thyroid carcinomas are differentiated and have a good prognosis. Clinical symptoms are relatively unspecific, however imaging and laboratory testing can often provide evidence for diagnosis of thyroid carcinoma. Therapy typically involves surgery, ablative radioiodine therapy and subsequent suppressive hormone substitution. The pillars of follow-up are diagnostic scintigraphy, sonography and laboratory tests. Redifferentiation or a change of the tracer can make dedifferentiated tumors again susceptible to nuclide therapy. New treatment options have become available with the introduction of tyrosine kinase inhibitors.